Case Report: Minimal Neurological Deficit of Two Adult Patients With Weston–Hurst Syndrome Due to Early Craniectomy: Case Series and Review of Literature on Craniectomy - Loesch-Biffar, Anna Mira; Junker, Andreas; Linn, Jennifer; Thon, Niklas; Heck, Suzette; Ottomeyer, Caroline; Straube, Andreas; Pfister, Hans Walter (Frontiers in Neurology, 2021)
Objectives: We describe two new cases of acute hemorrhagic leucoencephalitis (AHLE), who survived with minimal sequelae due to early measures against increased intracranial pressure, particularly craniotomy. The recently published literature review on treatment and outcome of AHLE was further examined for the effect of craniotomy. Methods: We present two cases from our institution. The outcome of 44 cases from the literature was defined either as good (no deficit, minimal deficit/no daily help) or poor outcome (severe deficit/disabled, death). Patients with purely infratentorial lesions (n = 9) were excluded. Fisher's exact test was applied. Results: Two cases are presented: A 43-year-old woman with rapidly progressive aphasia and right hemiparesis due to a huge left frontal white matter lesion with rim contrast enhancement. Pathology was consistent with AHLE. The second case was a 56-year-old woman with rapidly progressive aphasia and right hemiparesis. Cranial MRI showed a huge left temporo-occipital white matter lesion with typical morphology for AHLE. Both patients received craniotomy within the first 24 h and consequent immunosuppressive-immunomodulatory treatment and survived with minimal deficits. Out of 35 supratentorial reported AHLE cases, seven patients received decompressive craniotomy. Comparing all supratentorial cases, patients who received craniotomy were more likely to have a good outcome (71 vs. 29%). Conclusion: Due to early control of the intracranial pressure, particularly due to early craniotomy; diagnosis per biopsy; and immediate start of immunosuppressive-immunomodulatory therapies (cortisone pulse, plasma exchanges), both patients survived with minimal sequelae. Craniotomy plays an important role and should be considered early on in patients with probable AHLE.